The hole in the sky man's threat to the ozone layer (Toronto ; New York Bantam Books, 1988)
Reports on the threats to the ozone layer as confirmed in the findings of the National Airborne Ozone Expedition (NOZE) in Antarctica in 1986. Discusses past and present experiments and studies on the ozone layer, including ways and means to present f urther damage.
Includes bibliographical references and index.
Keywords: Air -- Pollution -- Environmental aspects; Ozone layer depletion; Air -- Pollution -- Environmental aspects; Ozone layer depletion